SnS nanoparticles electrostatically anchored on three-dimensional N-doped graphene as an active and durable anode for sodium-ion batteries. Issue 8 (2nd August 2017) - Xiong, Xunhui; Yang, Chenghao; Wang, Guanhua; Lin, Yuwei; Ou, Xing; Wang, Jeng-Han; Zhao, Bote; Liu, Meilin; Lin, Zhang; Huang, Kevin
Abstract : SnS nanoparticles (SnS NPs) electrostatically anchored on a 3D N-doped graphene (3DNG) network exhibit the best cycling performance reported so far for SnS-based anodes. Abstract : SnS nanoparticles (SnS NPs) electrostatically anchored on a 3D N-doped graphene (3DNG) network exhibit the best cycling performance reported so far for SnS-based anodes. The stronger affinity of 3DNG to SnS NPs and to the discharge product compared to pure graphene is the fundamental reason for achieving a stable electrode architecture during cycling.